Successful Treatment of Pseudoseptic Arthritis Contained Massive Purulent Fluid with Adalimumab in Rheumatoid Arthritis - Chung, Chong Hyuk; Lee, Myeung Su; Lee, Chang-Hoon (Chonnam medical journal, 2020)
KCI Citation Count: 0